Analisis Portofolio Saham Syariah Optimal dengan Pendekatan Sharia Compliant Asset Pricing Model (SCAPM) - Febrin Ayu Salsabila; Radia Purbayati; Fifi Afiyanti Tripuspitorini (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study is to determine the sharia stock portfolio that can be formed using the Sharia Compliant Asset Pricing Model (SCAPM) from 2017-2021. SCAPM is a modified form of CAPM which aims to frame the analytical model within the sharia framework. This research is descriptive quantitative research. The sample used is 13 Islamic stocks selected using purposive sampling method. The data used is secondary data obtained from the official websites of the Indonesia Stock Exchange, Bank Indonesia, and Investing.com. The software used to process the data is Microsoft Excel. The research result shows that there are 4 stocks that qualified for optimum stock portfolio, namely ADRO, ANTM, EXCL, and INCO. The largest proportion of funds held by ANTM (39,38%) while the lowest held by EXCL (13,04%) of the total funds.